Seedling root architecture and its relationship with seed yield across diverse environments in Phaseolus vulgaris - Strock, Christopher F.; Burridge, James D.; Massas, Anica Sandra F.; Beaver, James S.; Beebe, Stephen E.; Camilo, Samuel A.; Fourie, Deidre; Jochua, Celestina; Miguel, Magalhaes; Miklas, Phillip N.; Mndolwa, Eninka; Nchimbi-Msolla, Susan; et al. (Elsevier, 2019)
Seedling root phenotypes may have important impacts on fitness and are more easily measured than mature root phenotypes. We phenotyped the roots of 577 genotypes of common bean (Phaseolus vulgaris), representing the bulk of the genetic diversity for recent cultivars and landraces in this species. Root architectural phenotypes of seedlings germinated for nine days were compared to root architectural phenotypes in the field as well as seed yield across 51 environments with an array of abiotic stresses including drought, nutrient deficiency, and heat, as well as non-stress conditions. We observed repeatability ranging from 0.52–0.57 for measures of root phenotypes in seedlings, significant variation in root phene states between gene pools and races, relationships between seedling and field phenotypes, and varying correlations between seedling root phenes and seed yield under a variety of environmental conditions. Seed yield was significantly related to seedling basal root number in 22% of environments, seedling adventitious root abundance in 35% of environments, and seedling taproot length in 12% of environments. Cluster analysis grouped genotypes by their aggregated seedling root phenotype, and variation in seed yield among these clusters under non-stress, drought, and low fertility conditions was observed. These results highlight the existence and influence of integrated root phenotypes for adaptation to edaphic stress, and suggest root phenes have value as breeding targets under real-world conditions.